2017
DOI: 10.1007/s11010-017-3013-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polyunsaturated fatty acids and antioxidant vitamins on atrial oxidative stress, nitrotyrosine residues, and connexins following extracorporeal circulation in patients undergoing cardiac surgery

Abstract: Cardiac surgery with extracorporeal circulation is characterized by different degrees of myocardial ischemia/reperfusion, which is often associated with postoperative atrial fibrillation (POAF). We have previously shown that a novel preventive therapy based on the reinforcement of the antioxidant system using omega-3 fatty acids plus antioxidant vitamin supplementation applied to patients undergoing cardiac surgery reduces POAF occurrence. We hypothesized that oxidative stress and nitrosative stress are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…In addition, it has been reported recently that treatment with omega-3 PUFA and antioxidant vitamins reduces oxidative and nitrosative stress and prevents Cx40/Cx43 lateralization in human atrial tissue, which likely contributes to POAF prevention. However, it failed to fully prevent POAF occurrence, due to the fact that these compounds did not normalize Cx40 down-regulation and Cx45 up-regulation, that may promote POAF [ 85 ].…”
Section: Potential Targets Of Omega-3 Pufas Relevant To Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been reported recently that treatment with omega-3 PUFA and antioxidant vitamins reduces oxidative and nitrosative stress and prevents Cx40/Cx43 lateralization in human atrial tissue, which likely contributes to POAF prevention. However, it failed to fully prevent POAF occurrence, due to the fact that these compounds did not normalize Cx40 down-regulation and Cx45 up-regulation, that may promote POAF [ 85 ].…”
Section: Potential Targets Of Omega-3 Pufas Relevant To Arrhythmiamentioning
confidence: 99%
“…It appears that the anti-arrhythmic effect of beta-adrenergic blockers (often used in heart disease patients) may interfere with the anti-arrhythmic effect of omega-3 PUFAs. An attenuation of an abnormal Cx43 distribution by omega-3 PUFAs resulted in a reduction in POAF incidence [ 85 ].…”
Section: Anti-arrhythmic Efficacy Of the Omega-3 Pufasmentioning
confidence: 99%
“…Oxidative stress is induced by reactive oxygen species (ROS) that can damage cells and result in diseases such as diabetes, cardiovascular ailments, cancer, and liver damage [ 5 ]. Anti-oxidant vitamins and enzymes, such as superoxide dismutase, glutathione peroxidase, and glutathione reductase, can reduce excessive ROS production [ 6 ]. Phytochemicals with distinct flavors, odors, and colors can also exhibit anti-oxidant activities, and it has been reported that berries contain many phytochemicals such as a flavonoids, anthocyanins, and phenolic acids [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, oxidative stress is involved in the mechanism of AF in the following three aspects: atrial electrical remodeling, structural remodeling and connexin remodeling. [23][24][25][26] Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is a serine threonine kinase and can be oxidized by ROS at methionine residues 281/282 and then transform to ox-CaMKII which is associated with cardiovascular disease. 27 Additionally, ox-CaMKII was identified as a proarrhythmic signal because of promoting delayed afterdepolarizations (DADs) in Ang II infusion.…”
Section: Discussionmentioning
confidence: 99%